Entre rios e floresta: do povoado de Terruã à cidade de Pauini-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
This study seeks to understand the city of Pauini in the urban net of the gutter of the river Purus. Her space formation and location are objects of this research. Pauini is located in the gutter of the river Purus, to the Southwest of Amazon. We will leave of the changes and permanence, since the year from 1949 to 2020, analyzing the services presented in this municipality, originating from of the progress of the techniques that they appear in the city with the changes, on a migration period for the high rivers of the Amazonian and the occupation of the places to the city formation. Those factors raise it a cycle of Jesuit evangelizations and in the high rivers Madeira, Juruá and Purus, interlinked to the eraser production in the Amazonian. That process influences in the demographic density of the city, when the workers migrate of the rubber plantations for Pauini at the end of the year of 1960 for the drop search of the eraser, with crescent migratory movement towards the city due to the increase of the offer of the basic services (school, health and infrastructure) starting from the decade of 1970. The changes are not necessarily a rupture, they involve different subjects, molding and being moulded in the geographical space. The relationship particularized between man and nature, intensified in the area by the direct relationship with rivers and forest, she does of the small singular Amazonian city. The demographic growth seems to present signs of what is called development or progress in the city starting from the importance that she will carry out in the urban net of the area. Starting from literary revision on the urban space, field researches were accomplished in two moments. During the first wave of the pandemic, among the months of January to march of 2020 to september and november of 2021, following all of safety's protocols and health against the virus (COVID19), with application of 250 questionnaires divided among residents, (new and old), government and municipal institutions in the city of Pauini and Manaus. On the qualitative and quantitative indicators, the emergence of services can be denoted as the bank employee, internet and movable telephony, which can be considered "late" in a logic of a national scale. However, that is the specific time of Pauini, the time of her social construction originating from of the agents' space production. And that time influences directly in the changes happened in the urban space. It’s a slow time, it is not necessarily late, but that obeys it a logic of own reproduction, the agents' of Pauini logic, involved in the dynamics of the city by the importance in Rio Purus's urban net.
Keywords: Pesquisa sobre municípios - Pauini (AM); Cidades e vilas - Condições sociais - Pauini (AM); Urbanização - História - Pauini (AM); CIENCIAS HUMANAS: GEOGRAFIA: GEOGRAFIA HUMANA; Rede urbana; Rio Purus; Terruã; Pauini; Amazonas